Land Fragmentation and Food Insecurity in Ethiopia - Knippenberg, Erwin; Jolliffe, Dean; Hoddinott, John (World Bank, Washington, DC, 2018)
This paper revisits the economic consequences of land fragmentation, taking seriously concerns regarding the exogeneity of fragmentation, its measurement and the importance of considering impacts in terms of welfare metrics. Using data that are well-suited to addressing these issues, the analysis finds that land fragmentation reduces food insecurity. This result is robust to how fragmentation is measured and to how exogeneity concerns are addressed. Further, the paper finds that land fragmentation mitigates the adverse effects of low rainfall on food security. This is because households with diverse parcel characteristics can grow a greater variety of crop types.